The Impact of Ethnic-Immigrant Status and Obesity-Related Risk Factors on Behavioral Problems among US Children and Adolescents - Gopal K. Singh; Stella M. Yu (Scientifica)
We examined the prevalence and correlates of parent-reported behavioral problems among immigrants and US-born children aged 6–17 years. The 2007 National Survey of Children’s Health was used to develop an 11-item factor-based behavioral problems index (BPI) and a dichotomous serious behavioral problems (SBP) measure. Logistic and least-squares regression and disparity indices were used to analyze differentials. BPI scores varied from 92.3 for immigrant Asian children to ≥102.4 for native Hispanic and Black children. The prevalence of SBP ranged from 2.9% for immigrant Asian children to 17.0% for native Black children. Children in most ethnic-immigrant groups had higher adjusted levels of behavioral problems than immigrant Asian children. Native Hispanic children, native and immigrant White children, immigrant Black children, and native Asian children had ≥3.0 times higher adjusted odds of SBP than immigrant Asian children. Lower socioeconomic status, obesity, physical inactivity, lack of sports participation, increased television viewing, and sleep disruption were associated with greater behavioral problems. Sociodemographic and behavioral factors accounted for 37.0% and 48.5% of ethnic-immigrant disparities in BPI and SBP, respectively. Immigrant children had fewer behavioral problems than native-born children. Policies aimed at modifying obesity-related behaviors and social environment may lead to improved behavioral/emotional health in both immigrant and native children.